Muscle strength in adolescent men and risk of cardiovascular disease events and mortality in middle age: a prospective cohort study - Timpka, Simon (BioMed Central, 2014)
BACKGROUND: Ischemic heart disease and stroke are two severe types of cardiovascular disease (CVD), a major contributor to the global burden of disease. The preventive framework currently includes promotion of both adequate cardiorespiratory and muscular fitness. Although muscle fitness is established as an indicator of health, it is currently unknown whether muscle strength is associated with later CVD independently of cardiorespiratory fitness. METHODS: We studied 38,588 Swedish men who in 1969 to 1970 (typically aged 18 years) completed compulsory conscription. Using the mean standardized score of three isometric muscle strength tests performed at conscription (hand grip, elbow flexion and knee extension), we categorized the subjects into three groups with the 25th to 75th percentile defining the reference category. We followed the cohort until 2012 for diagnosed CVD events and mortality via national health care registers and the national cause of death register. To estimate hazard ratios (HR) for CVD events (coronary heart disease or stroke) and CVD mortality we used Cox proportional hazard models adjusted for body mass index, smoking, alcohol consumption, cardiorespiratory fitness and socioeconomic status. RESULTS: Men with high muscle strength in adolescence had a decreased risk of later CVD events (HR 0.88, 95% confidence interval 0.77 to 0.99), whereas we observed no increased risk in men with low muscle strength (0.99, 0.86 to 1.13). However, low muscle strength was associated with increased risk of CVD mortality during middle age (1.31, 1.02 to 1.67). CONCLUSIONS: Muscle strength in adolescent men is inversely associated with later CVD events and CVD mortality in middle age, independently of cardiorespiratory fitness and other important confounders. Thus, the role of muscle fitness in the prevention and pathogenesis of CVD warrants increased attention.